Computational structural analysis of spatial multibody systems based on mobility criteria. (October 2022) - Celdran, A.; Saura, M.; Dopico, D.
Abstract: Computational efficiency is a critical aspect of multibody dynamics. Recent developments in linear algebra libraries and hardware architectures allow the multibody community to improve the performance of their kinematic and dynamic formulations. Kinematic substructuring of multibody systems may take great advantage of these resources by dividing the multibody system into modules that can be solved more efficiently than the whole set of equations of the multibody system at once. This work discusses some advantages of the kinematic substructuring based on mobility criteria over methods based on linear graph theory. It also introduces detailed information on the algorithms we have developed for the computational structural analysis of planar and spatial multibody systems. Structural transformations easily generate different kinematic substructures, ordered and classified under various criteria depending on the analyst's needs, such as robustness and efficiency. A graphical user interface may guide the analyst while defining the topology of the multibody system and show detailed information about the obtained results. The algorithms are explained through an example, and the advantages of this method are reinforced as applied to several spatial multibody systems. Highlights: Mobility-based kinematic substructuring advantages over linear graph theory. Detailed algorithms for computational structural analysis of multibody systems. Automatic ordering of kinematic substructures depending on the analyst's needs. Only an extended adjacency matrix is needed to define the multibody system's topology. Algorithms explained through a case study and applied to complex spatial multibody systems.